Analysis of Physical Activity on The Body Mass Index and Mental Health Score Using an IoT-based Mobile Application (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The rapid advancement of digital technology has contributed to increased sedentary behavior among adolescents, characterized by prolonged screen exposure and minimal physical activity. Sedentary lifestyles are strongly associated with adverse health outcomes, including obesity, musculoskeletal disorders, cardiovascular disease, metabolic abnormalities, and psychological conditions such as stress, anxiety, and depression. Atherosclerotic cardiovascular disease, in particular, remains a leading cause of mortality, accounting for approximately 32% of deaths worldwide[1]. This study aimed to evaluate the effects of brisk walking on body mass index (BMI) and mental health among sedentary adolescents using an IoT-based mobile application for activity monitoring. A randomized controlled trial was conducted involving adolescents divided into four groups: low-, moderate-, and high-intensity brisk walking interventions, and a control group. The intervention was carried out over four weeks with weekly follow-ups. Univariate analysis showed that mean BMI decreased by 0.9±0.3kg/m² in the moderate-intensity group and by 1.4±0.4kg/m² in the high-intensity group, compared with no significant change in the control group (0.1±0.2kg/m²). Similarly, the mean mental health score, assessed using a standardized scale, improved significantly, with a reduction of 6.2±2.1 points in the moderate-intensity group and 8.5±2.4 points in the high-intensity group (p<0.01). Bivariate analysis confirmed significant correlations, indicating that higher brisk walking intensity was associated with lower BMI (r=−0.42, p<0.01) and reduced mental health scores (r=−0.47, p<0.01), demonstrating an inverse relationship between physical activity intensity and both outcomes. These findings highlight the effectiveness of IoT-based monitoring in capturing sedentary behavior and physical activity patterns, while demonstrating that regular brisk walking yields significant benefits for both physical and mental health. The integration of such technology-driven interventions into adolescent health programs represents a promising preventive strategy against cardiovascular disease and related disorders.